On the use of NDT data for reliability-based assessment of existing timber structures - Sousa, Hélder S. (2013)
The objective of this paper is to address the possibilities of using non-destructive testing (NDT) data for updating information and obtaining adequate characterization of the reliability level of existing timber structures and, also, for assessing the evolution in time of performance of these structures when exposed to deterioration. By improving the knowledge upon the mechanical properties of timber, better and more substantiated decisions after a reliability safety assessment are aimed at. Bayesian methods are used to update the mechanical properties of timber and reliability assessment is performed using First Order Reliability Methods (FORM). The results show that different degrees of belief in the updating data may significantly influence the reliability level. The updating data to be used are NDT results obtained with ultrasound, resistance drilling and pin penetration equipments. The tests were conducted on chestnut wood (Castanea sativa Mill.) specimens, and were combined with tests to determine the compressive strength parallel to the grain. The uncertainty of the different NDT results is modeled by Maximum Likelihood estimates. Resistance distributions functions are considered to analyze the difference before and after updating by NDT, showing that lower variations may typically be obtained with the new information. Moreover, updating of the parameters in different deterioration models is considered in order to be able to evaluate the time dependency of the reliability, and information of NDT is also used to calibrate these models. The proposed approach is used for reliability assessment of different structural timber systems. Reliability of the structural system is assessed regarding the failure consequences of individual elements defined as key elements which were determined by their influence on the cross section loss. The results given by the pin penetration tests were the most similar to the reference experimental model with statistic parameters given by the results of destructive tests. The resistance drilling and ultrasound updating schemes led to higher level of reliability than the reference model values, therefore these updating data should be considered with caution, as they can result in unsafe results for the reliability compared to the reference models.